Cerebral Amyloidosis: Postmortem Detection with Human 7.0-T MR Imaging System - van Rooden, Sanneke; Maat-Schieman, Marion L. C.; Nabuurs, Rob J. A.; van der Weerd, Louise; van Duijn, Sara; van Duinen, Sjoerd G.; Natté, Remco; van Buchem, Mark A.; van der Grond, Jeroen (Radiology, 2009)
To explore the ability of whole-body 7.0-T magnetic resonance (MR) imaging to depict differences in aspects of the cerebral cortex of postmortem human brain specimens with cerebral amyloid beta deposition in connection with Alzheimer disease (AD), Down syndrome, or sporadic or hereditary cerebral amyloid angiopathy (CAA) and control brain specimens lacking such deposition. This study was approved by the local institutional review board. In all cases, informed consent was obtained to perform autopsy and to use the tissues for research purposes. T2- and T2*-weighted MR imaging was performed in formalin-fixed samples of brain tissue from six subjects with AD changes, seven with CAA, and five subjects without immunohistochemical evidence of cerebral amyloid beta deposition. All MR images were visually assessed for hypointense foci in and inhomogeneity of the cortex. Sensitivity, specificity, and kappa values of these MR imaging features in the detection of histologic changes were calculated. High-spatial-resolution 0.3 x 0.3 x 0.3-mm three-dimensional T2*-weighted images revealed hypointense foci, inhomogeneity of the cortex, or both in all specimens with brain amyloid beta deposition. These MR imaging features were observed in none of the control specimens. The finding of postmortem susceptibility-weighted changes in the cerebral cortex of patients with cerebral amyloidosis with a human 7.0-T MR imaging system opens up the possibility of obtaining in vivo radiologic evidence of cerebral amyloid beta deposition.